Urinary polycyclic aromatic hydrocarbon metabolites were associated with short sleep duration and self-reported trouble sleeping in US adults: data from NHANES 2005–2016 study population - Han, Lu; Wang, Qi (Frontiers in Public Health, 2023)
Background The aim of the current study was to investigate the link between human exposure to PAHs with short sleep duration (SSD) and self-reported trouble sleeping. Methods A total of 9,754 participants and 9,777 participants obtained from NHANES 2005–2016 were included in this cross-sectional study about SSD and self-reported trouble sleeping, respectively. The association between urinary PAHs metabolites with the prevalence of SSD and self-reported trouble sleeping by the weighted multivariate logistic regression model, restricted cubic spline (RCS) curves, and weighted quantile sum (WQS) regression. Results After adjusting for all covariates, 1-hydroxynapthalene, 2-hydroxynapthalene, 3-hydroxyfluorene, 2-hydroxyfluorene, 1-hydroxyphenanthrene, and 1-hydroxyphenanthrene demonstrated positive associations with SSD prevalence. Besides, 1-hydroxynapthalene, 2-hydroxynapthalene, 3-hydroxyfluorene, 2-hydroxyfluorene, 1-hydroxyphenanthrene, and 1-hydroxyphenanthrene exhibited positive associations with the prevalence of self-reported trouble sleeping following the adjustment for all covariates. RCS curves confirmed the non-linear associations between 1-hydroxynapthalene, 2-hydroxynapthalene, 3-hydroxyfluorene, 2-hydroxyfluorene, and 1-hydroxyphenanthrene with the prevalence of SSD, and 1-hydroxynapthalene, 3-hydroxyfluorene, and 2-hydroxyfluorene with the prevalence of self-reported trouble sleeping. The WQS results showed that mixed exposure to PAH metabolites had a significant positive association with the prevalence of SSD (OR: 1.087, 95% CI: 1.026, 1.152, p = 0.004) and self-reported trouble sleeping (OR: 1.190, 95% CI: 1.108, 1.278, p < 0.001). Conclusion Urinary concentrations of PAH metabolites exhibited a close association with the prevalence of SSD and self-reported trouble sleeping in US adults. More emphasis should be placed on the importance of environmental effects on sleep health.